Bacteriocin Activity of Lactic Acid Bacteria from Giant Prawn (Macrobrachium rosenbergii) - Della Meysari; Henny Helmi; Rahmad Lingga (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
AbstractFood is one of the necessities of life. Food is often added with preservatives such as chemicals that harm human health. One of the safe natural preservatives is bacteriocin compounds. Bacteriocins can be produced by lactic acid bacteria (LAB). These bacteriocins have known as Generally Recognized as Safe (GRAS) status. This study aimed to isolate and identify BAL from the digestive tract of giant shrimp (Macrobrachium rosenbergii), as well as test the ability of the bacteriocin produced to the proteolytic enzyme, temperature, pH, and salt. The research methods used were bacterial isolation, bacterial characterization, hemolysis test, bacteriocin antibacterial activity tests, proteolytic enzyme influence tests on bacteriocin activity, temperature, pH, and salt content tests on bacteriocin activity, and antibiotic tests. The research results showed that there were 37 LAB isolates and there were 7 isolates that produced bacteriocins. The LAB isolated from the digestive tract of giant prawns is Gram-positive bacteria in the form of bacilli, catalase-negative, gamma hemolytic, methyl red positive, and homofermentative. The bacteriocins can inhibit the pathogenic bacteria Staphylococcus aureus and Escherichia coli and be degraded by the Protease-K enzyme. Moreover, the bacteriocins have the characteristics of being stable at acid to neutral pH (pH 2–7), stable at low and high temperatures (4–100 °C), and stable under conditions with a salt content of 2–6.5%. The results of the identification of LAB belonged to the Lactobacillus genus.AbstrakMakanan merupakan kebutuhan pokok dalam kehidupan sehari-hari manusia. Makanan sering kali ditambahkan bahan pengawet seperti bahan kimia yang berpengaruh buruk terhadap kesehatan manusia. Salah satu alternatif bahan pengawet alami yang aman bagi kesehatan manusia adalah senyawa bakteriosin. Bakteriosin dapat dihasilkan dari bakteri asam laktat (BAL). Bakteriosin yang diproduksi oleh BAL sudah berstatus Generally Recognized as Safe (GRAS). Penelitian ini bertujuan untuk mengisolasi dan mengidentifikasi BAL dari saluran pencernaan udang galah (Macrobrachium rosenbergii), serta menguji kemampuan bakteriosin yang dihasilkan terhadap enzim proteolitik, suhu, pH dan kadar garam. Metode penelitian yang dilakukan adalah isolasi bakteri, karakterisasi bakteri, uji hemolisis, uji aktivitas antibakteri bakteriosin, uji pengaruh enzim proteolitik, suhu, pH dan kadar garam terhadap aktivitas bakteriosin. Hasil isolasi terdapat 37 isolat BAL dan 7 isolat yang menghasilkan bakteriosin. BAL yang diisolasi dari saluran pencernaan udang galah merupakan bakteri Gram positif berbentuk basil, katalase negatif, gamma hemolisis, methyl red positif dan homofermentatif. Bakteriosin mampu menghambat bakteri patogen Staphylococcus aureus dan Escherichia coli, dapat didegradasi oleh enzim Protease-K, stabil pada pH asam hingga netral (pH 2–7), stabil pada suhu rendah maupun tinggi (4°–100 °C) dan stabil pada kondisi dengan kadar garam 2–6,5%. Hasil identifikasi BAL dari usus udang galah yaitu bakteri termasuk dalam Genus Lactobacillus.